Triagem neonatal como estratégia para o diagnóstico e tratamentoprecoces da toxoplasmose congênita em Belo Horizonte, Minas Gerais - Glaucia Manzan Queiroz de Andrade (2008)
Toxoplasmosis is prevalent in Brazil and presents regional variations depending on the lifestyle of the population. Primary toxoplasma infection during pregnancy can lead to neurological and ocular sequelae in the child, detectable after birth or manifesting later during growth. The severity of Latin American infected childrens ocular impairment, especially inBrazil, has been attributed, among other reasons, to differences on parasites strains. Experts state that regions with high prevalence should adopt prenatal screening and/or neonatal screening associated with educational health information, in order to control congenitaltoxoplasmosis. Eligible strategies should be regionally evaluated to increase efficacy. Objectives: This study aims to determine the prevalence of congenital toxoplasmosis in Belo Horizonte by screening (Toxoplasma-specific IgM) on live births, verifying this strategys contribution to the early diagnoses of the disease. Infected children were followed during three years, during which ocular and hearing impairment were evaluated. Methods: During one year (2003-2004), a cross-sectional study was performed on 31.808 newborn children dried-blood samples (95% of live births in the period), routinely sent to newborn screeningprograms in Belo Horizonte. These samples were tested for the presence of T. gondii specific IgM. When the screening was positive or indeterminate, serum samples from mother and child were requested for confirmatory serology. Congenital toxoplasmosis was confirmed bypresence of IgM and/or IgA positive within the first six months if associated to positive IgM and IgG in the mother or by the presence of IgG at 12 months of age. Specific treatment was given to all children (free of charge) during one year and the infant underwent exams to evaluate the dimension of their impairment. Results: Congenital toxoplasmosis prevalence in Belo Horizonte was 1/1.590 live born infants (0.06%), which are considered high. Twenty infected children were detected. Half of them were identified exclusively by neonatal screening, which also identified 77% of the children with sub clinic infection. After three years, retinochoroiditis lesions were found in 78.9% of the children and sensorineural hearing loss in 21.1%. After the first year of life three children presented new ocular lesions, and one of them hadnt had ocular impairment before. Most pregnant women presented seroconversion between the 2nd and 3rd trimester of pregnancy and didnt receive any orientation about how to avoid the sources of the infection during prenatal. Toxoplasmosis risk factors among mothers of the studied sample were: no prophylactic orientation during prenatal, eating raw or undercooked meat, eating raw or undercooked egg and owning cats. Conclusions: Congenital toxoplasmosis is prevalent in Belo Horizonte, often causing impairment of vision and hearing. Neonatal screening was feasible and low cost when associated with the already existing newborn screening program. It identified cases of infection undetected by prenatal screening, especially when the infection was sub clinic and allowed early treatment of infected children. The high frequency of ocular lesion, with considerable morbidity, showed the need to adopt a strategy to control the infection, ideally prenatal screening, but now it could be associated with neonatal screening.